Coral reefs of the turbid inner-shelf of the Great Barrier Reef, Australia: An environmental and geomorphic perspective on their occurrence, composition and growth - Browne, Nicola; Smithers, S.; Perry, C. (Elsevier, 2012)
Investigations of the geomorphic and sedimentary context in which turbid zone reefs exist, both in the modern and fossil reef record, can inform key ecological debates regarding species tolerances and adaptability to elevated turbidity and sedimentation. Furthermore, these investigations can address critical geological and palaeoecological questions surrounding longer-term coral-sediment interactions and reef growth histories. Here we review current knowledge about turbid zone reefs from the inner-shelf regions of the Great Barrier Reef (GBR) in Australia to consider these issues and to evaluate reef growth in the period prior to and post European settlement. We also consider the future prospects of these reefs under reported changing water quality regimes. Turbid zone reefs on the GBR are relatively well known compared to those in other reef regions. They occur within 20 km of the mainland coast where reef development may be influenced by continual or episodic terrigenous sediment inputs, fluctuating salinities (24–36 ppt), and reduced water quality through increased nutrient and pollutant delivery from urban and agricultural runoff. Individually, and in synergy, these environmental conditions are widely viewed as unfavourable for sustained and vigorous coral reef growth, and thus these reefs are widely perceived as marginal compared to clear water reef systems.However, recent research has revealed that this view is misleading, and that in fact many turbid zone reefs in this region are resilient, exhibit relatively high live coral cover (> 30%) and have distinctive community assemblages dominated by fast growing (Acropora, Montipora) and/or sediment tolerant species (Turbinaria, Goniopora, Galaxea, Porites). Palaeoecological reconstructions based on the analysis of reef cores show that community assemblages are relatively stable at millennial timescales, and that many reefs are actively accreting (average 2–7 mm/year) where accommodation space is available, despite recent anthropogenic pressures. These turbid zone reefs challenge traditional views on the environmental conditions required for active reef growth, but given their proximity to land and associated stresses, current knowledge on these less well understood reefs should be synthesised to aid coastal management directives. Terrigenous sediments are a dominant influence on turbid zone reef occurrence, composition and growth, and, therefore, the assessment of their future prospects will require a detailed understanding of the sedimentary regimes under which they occur and of their differential response modes.